Quality Assurance of Total Carotenoids and Quercetin in Marigold Flowers (Tagetes erecta L.) as Edible Flowers - Kusumiyati Kusumiyati; Ine Elisa Putri; Yuda Hadiwijaya; Agitha Kartika; Yusuf Eka Maulana; Wawan Sutari (International Journal of Food Science)
Marigold flowers, which are also known as Tagetes erecta L., are widely recognized for their bright colors and health benefits. Therefore, the purpose of this research was to investigate the quality of total carotenoid content (TCC) and quercetin in marigold flowers, specifically the edible ones, using visible near-infrared spectroscopy (Vis-NIRS) technology. Both bioactive compounds in these flowers were assessed using Vis-NIRS. The technology is considered to be a rapid and non-destructive method for evaluating the quality of agricultural products. To ensure accuracy in the evaluation, Vis-NIRS was validated against conventional methods such as spectrophotometry and chromatography. The results showed that the use of Vis-NIRS helped to accurately determine the levels of TCC and quercetin in marigold flowers. Based on the analysis results, the best accuracy values for TCC were as follows: the correlation coefficient of the calibration set (Rcal) was 0.94, the root mean square error of the calibration set (RMSEC) was 125.57, the correlation coefficient of the prediction set (Rpred) was 0.87, the root mean square error of the prediction set (RMSEP) was 129.35, and the ratio of prediction to deviation (RPD) was 2.77. For quercetin, the best accuracy values were: Rcal was 0.96, RMSEC was 1.63, Rpred was 0.88, RMSEP was 2.37, and RPD was 2.09. These results demonstrate that the method provides a reliable alternative to destructive method. The research showed that Vis-NIRS served as a reliable quality assurance tool for assessing bioactive compounds in marigold flowers.